Comparative study on the perspective towards the benefits and hindrances of implementing building information modelling (Bim) - Ern, P.A.S. (Penerbit UTHM, 2020)
Building Information Modelling (BIM) is considered one of the most effective technologies to improve the productivity of the building process. BIM has proven its advantages throughout the building project life cycle. However, the lack of awareness towards BIM is due to the persistent practice of obsolete technology in construction. Thus, the aim of this study is to explore the industrial practitioners' perspectives on the benefits and hindrances of BIM implementation in order to understand their level of awareness. A questionnaire survey was distributed to 120 consultant companies in Kuala Lumpur where 52 responded. The data were analysed using frequency analysis and test for correlation was performed. Results revealed that respondents have a positive awareness of the benefits and hindrances towards the implementation of BIM. Both BIM and non-BIM users achieve a significant agreement on the benefits of BIM to control delay, cost, and improves management. On the other hand, all participants criticised that High Cost Allocation, Time Consuming, Lack of Information are hindering the implementation of BIM. In addition, there was a weak relationship between the BIM as a tool in company and the predictor variables which are level of understanding, time saving, cost saving, better management, cost allocation, time consumption and lack of awareness. The correlation coefficient values obtained were 0.419, 0.403, 0.376, 0.446, 0.324, 0.407 and 0.274 respectively. The outcomes indicate that construction industry experience constraint on implementing BIM mainly due to the BIM enforcement by the government industry. Thus, this paper is significant in contributing knowledge of awareness between BIM and non-BIM users on benefits and hindrances of BIM implementation. It also acts as a benchmark for the government to address the relevant issues provide a channel to drive the industry towards BIM level 2. Â© Universiti Tun Hussein Onn Malaysia Publisherâs Office.